Cytokine Stimulation of MUC4 Expression in Human Female Reproductive Tissue Carcinoma Cell Lines and Endometrial Cancer. Issue 11 (9th September 2015) - Chapela, Patricia J.; Broaddus, Russell R.; Hawkins, Shannon M.; Lessey, Bruce A.; Carson, Daniel D.
ABSTRACT: MUC4, a transmembrane glycoprotein, interferes with cell adhesion, and promotes EGFR signaling in cancer. Studies in rat models have demonstrated steroid hormonal regulation of endometrial MUC4 expression. In this study, qRT‐PCR screening of mouse tissues determined that Muc4 mRNA also was robustly expressed in mouse uteri. Previous studies from our labs have demonstrated MUC4 mRNA was expressed at levels <1% of MUC1 mRNA in human endometrium and endometriotic tissue. Multiple human endometrial adenocarcinoma cell lines were assayed for MUC4 mRNA expression revealing extremely low basal expression in the Ishikawa, RL‐95‐2, AN3CA, and KLE lines. Moderate to high expression was observed in HEC50 and HEC‐1A cells. MUC4 mRNA expression was not affected by progesterone and/or estrogen treatment, but was greatly stimulated at both mRNA and protein levels by proinflammatory cytokines (IFN‐γ and TNF‐α), particularly when used in combination. In endometrial tissue, MUC4 mRNA levels did not change significantly between normal or cancerous samples; although, a subset of patients with grade 1 and 2 tumors displayed substantially higher expression. Likewise, immunostaining of human endometrial adenocarcinoma tissues revealed little to no staining in many patients (low MUC4), but strong staining in some patients (high MUC4) independent of cancer grade. In cases where staining was observed, it was heterogeneous with some cells displaying robust MUC4 expression and others displaying little or no staining. Collectively, these observations demonstrate that while MUC4 is highly expressed in the mouse uterus, it is not a major mucin in normal human endometrium. Rather, MUC4 is a potential marker of endometrial adenocarcinoma in a subset of patients. J. Cell. Biochem. 116: 2649–2657, 2015. © 2015 Wiley Periodicals, Inc.